A review of the neuroprotective effects of andrographolide in Alzheimer's disease - Abedi, Zahra; Hassan, Zurina; Basri, Hamidon; Inche Mat, Liyana Najwa; Khaza’ai, Huzwah; Mohamad, Nur Afiqah (Springer, 2021)
Alzheimer’s disease, characterized by amyloid beta peptides and neurofibrillary tangles, is the most prevalent cause of dementia. Nowadays, some novel medicines being developed have displayed more illustrious therapeutic efficacies in Alzheimer’s disease. Recent studies have found andrographolide exhibiting therapeutic efficacy in a variety of Alzheimer’s disease models. Andrographolide is a traditional herbal medicine compound extracted from Andrographis paniculata. Evidence has shown that andrographolide reduces amyloid beta aggregation and suppresses neuroinflammatory response and synaptic dysfunction by reversing the microglia-mediated production of pro-inflammatory cytokines as well as Alzheimer’s disease-associated reduction in synaptic proteins. In the present review, the pharmacological effects of andrographolide are summarized and its mechanism of action against Alzheimer’s disease is discussed to discover the possibilities of andrographolide for Alzheimer’s disease prevention and therapy.